Pembangunan model kurikulum m-Pembelajaran kursus teknologi dalam pengajaran dan pembelajaran di Institut Pendidikan Guru - Muhammad Nidzam, Yaakob (2017)
The m-Learning Model development is able to improve students’ performance achievement. Yet, studies involving m-Learning in education are very limited because most studies are more focused on the digital function of mobile devices rather than mobile pedagogy. Therefore, this study is aimed at examining the implementation of the m-Learning curriculum which is in line with the current educational needs at the Malaysian Teacher Education Institute and should be carried out as an initiative and provision of infrastructure at schools as well as institutions of higher learning.This ongoing agenda of the Ministry of Education needs to be given support and realization. This study identifies the needs of the m-Learning curriculum model for the teaching and learning of a Technology course in the Malaysian Institute of Teacher Education. The main objective was to design a curriculum Model of m-Learning for a Technology course in teaching and learning using Fuzzy Delphi Technique.This study employed Design and Development Research (DDR) which involved descriptive statistics in the analysis of phase one. For phase two, data were analyzed using Fuzzy Delphi Technique that was Triangular Fuzzy Numbers and Defuzzification Process. This process was to determine the ranking of each of the variables and build a model. The third phase which was consumerism assessment involving analyzing qualitative findings. The findings of the first phase showed that the highest mean score was for the major component of the model (mean = 4.510) and the lowest was the purpose of using m-learning (mean = 3.715). This concluded that there was a need to develop a model for m-Learning in a Technology in teaching and learning course. The findings of the second phase showed that the panel of experts agreed unanimously on the elements in the model. The general findings of the third phase from the interviews of students and lecturers showed that they were satisfied with the use of m-Learning Model in the aspects of technology, usability and learning. This study implies that there is a need to develop a model of m-Learning in a Technology course in teaching and learning in the Teacher Education Institute, which is parallel with the development of ICT and the changes in the current pedagogy